Metaproteomics: Extracting and Mining Proteome Information to Characterize Metabolic Activities in Microbial Communities. Issue 1 (17th June 2014) - Abraham, Paul E.; Giannone, Richard J.; Xiong, Weili; Hettich, Robert L.
Abstract: Contemporary microbial ecology studies usually employ one or more "omics" approaches to investigate the structure and function of microbial communities. Among these, metaproteomics aims to characterize the metabolic activities of the microbial membership, providing a direct link between the genetic potential and functional metabolism. The successful deployment of metaproteomics research depends on the integration of high‐quality experimental and bioinformatic techniques for uncovering the metabolic activities of a microbial community in a way that is complementary to other "meta‐omic" approaches. The essential, quality‐defining informatics steps in metaproteomics investigations are: (1) construction of the metagenome, (2) functional annotation of predicted protein‐coding genes, (3) protein database searching, (4) protein inference, and (5) extraction of metabolic information. In this article, we provide an overview of current bioinformatic approaches and software implementations in metaproteome studies in order to highlight the key considerations needed for successful implementation of this powerful community‐biology tool. Curr. Protoc. Bioinform . 46:13.26.1‐13.26.14. © 2014 by John Wiley & Sons, Inc.